Response of Streamflow and Soil Erosion to Climate Change and Human Activities in Nam Rom River Basin, Northwest of Vietnam: DOI: 10.32526/ennrj.18.4.2020.39 - Le Huong, Hoang; Thanh Son, Ngo (Environment and Natural Resources Journal, 2020)
Change in climate and land use is the main cause of increasing streamflow and soil erosion. However, very few studies have investigated these changes on a basin scale. Thus, this study used the Soil and Water Assessment Tool (SWAT) method to evaluate the effects of both land use and climate change effects on streamflow, sediment yield, and soil loss in the Nam Rom River Basin, Northwest of Vietnam. The outputs of the SWAT model demonstrated it to be a strong tool in predicting catchment hydrology, sediment transport, and soil loss. Meanwhile, based on SWAT model simulation, it was found that reforestation and management practices executed between 1992 and 2015 strongly contributed to the decreased sediment yield. The potential for climate change clearly leads to an increase to sediment yield and significantly more soil loss. The combined climate and land use change analysis indicated that land use planning could be adopted to mitigate streamflow (16.9%) and sediment load (4.9%) in the future, in conjunction with the projected direct impact of climate change. In conclusion, the findings in the present study contribute useful knowledge, methods, and techniques that could be reapplied to other regions in Vietnam and the world in terms of land and water conservation.